Four new representatives of the genus Allocyclops Kiefer, 1932 from semi-consolidated subsoil aquifers in Benin (Copepoda, Cyclopoida, Cyclopidae) - Fiers, Frank; LAGNIKA, Moïssou (My University, 2015)
Several species of cyclopoid copepods were collected from improved and unimproved hang-dug-wells in the Republic of Bénin over the years 2009–2014. Fifty five wells located in seven different districts were sampled: 15 wells in the district of Pobè (Department Plateau) and 1 well in Kétou (Department Plateau), 4 wells in Porto-Novo District (Department Ouémé) and, 15 wells in Lokossa District (Department Mono),18 wells in Parakou District (Department Borgou), 1 well in Abomey-Calavi District (Department Atlantique) and 1 in Zogbodomè District (Department Zou). Among them, 4 new species of the genus Allocyclops Kiefer, 1932 were found and are described herein: Allocyclops spinifer sp. n., A. nudus sp. n., A. pilosus sp. n. and A. sakitii sp. n. They are compared with the three African species previously described. Allocyclops appears to be a sub-Saharan taxon specialized to thrive in the variable environment of subsoil aquifers in laterite deck beds. An identification key to the 7 different African Allocyclops species is provided.
Keywords: Copepoda; Cyclopidae; subterraneous; Bénin; new species; key; laterites